Konstruksi Sosial Keagamaan Atas Pemenuhan Kesejahteraan Masyarakat Lobo di Kelurahan Peta Kota Palopo - Tenrijaya Tenrijaya (Palita: Journal of Social Religion Research, 2021)
Abstract[English]:This research is entitled "Social Religious Construction on Fulfilling the Welfare of the Lobo Community in Peta Village, Palopo City". The focus of the research is how the social characteristics of the Lobo community, Peta sub-district, Palopo city; How is the socio-religious construction towards the fulfillment of the social welfare of the Lobo community in the Palopo urban village map. This research was designed with qualitative research using a sociological study approach, with data collection techniques of observation, interviews, and documentation. The results of this study indicate that 1). Social characteristics of the Lobo community in the Palopo city map can be seen from various angles including: location of the area, religious beliefs, population composition in terms of population, population composition in terms of education level, and population composition in terms of livelihoods. 2). The socio-religious construction of the fulfillment of the welfare of the people of Lobo, Palopo urban village, cannot be separated from several elements of the social structure that exist in the life of the people in Palopo city. The elements include: first, elements of the culture or customs of the Lobo community; second, elements of Palopo city government policies related to the development and religious welfare of the people of Palopo city and third, elements of socialization media and social religious movements of the community.Abstrak[Indonesia]:Penelitian ini berjudul “Konstruksi Sosial Keagamaan atas Pemenuhan Kesejahteraan Masyarakat Lobo di Kelurahan Peta Kota Palopo”. Fokus penelitiannya adalah bagaimana karakteristik sosial masyarakat Lobo kelurahan Peta kota Palopo; bagaimana konstruksi sosial keagamaan terhadap pemenuhan kesejahteraan sosial masyarakat Lobo kelurahan peta kota Palopo. Penelitian ini didesain dengan penelitian kualitatif mengunakan pendekatan studi kajian sosiologis, dengan teknik pengumpulan data observasi, wawancara, dan dokumentasi. Hasil penelitian ini menunjukkan bahwa 1). Karakteristik sosial masyarakat Lobo kelurahan Peta kota Palopo dapat dilihat dari berbagai sudut padang meliputi: letak wilayah, keyakinan agama, komposisi penduduk dari segi jumlah penduduk, komposisi penduduk dari segi tingkat pendidikan, dan komposisi penduduk dari segi mata pencaharian. 2). Konstruksi sosial keagamaan terhadap pemenuhan kesejahteraan masyarakat Lobo kelurahan Peta kota Palopo tidak lepas dari beberapa unsur-unsur struktur sosial yang ada dalam kehidupan masyarakat di kota Palopo. Adapun unsur-unsur tersebut meliputi: pertama, unsur kebudayaan atau adat istiadat masyarakat Lobo; kedua, unsur kebijakan-kebijakan pemerintah kota Palopo terkait dengan pengembangan dan kesejahteraan keagamaan masyarakat kota Palopo dan ketiga, unsur media sosialisasi dan gerakan-gerakan sosial keagamaan masyarakat.